Respuestas
Respuesta dada por:
1
Explicación paso a paso:
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 5 años
hace 5 años
hace 5 años
hace 8 años
hace 8 años
\begin{gathered} - 15 ya q si tenemos ( + 5).( - 3) hacemos \: la \: ley \: de \: signos \: y \: mas \:por \: menos \: es \: igual \: a \: menos \: entonces \: pasamos \: a \: multipilcar \\ ( + 5).( - 3) \\ = - 5. - 3 \\ = - 15\end{gathered}
−15yaqsitenemos(+5).(−3)hacemoslaleydesignosymaspormenosesigualamenosentoncespasamosamultipilcar
(+5).(−3)
=−5.−3
=−15